Attribution analysis of runoff evolution in Kuye River Basin based on the time-varying budyko framework - Huang, Tingting; Wang, Zhihui; Wu, Zhiyong; Xiao, Peiqing; Liu, Yu (Frontiers in Earth Science, 2023)
The underlying surface parameters in the Budyko framework (such as parameter n in the Choudhury–Yang equation) are crucial for studying the relationship between precipitation, evapotranspiration, and runoff. It is important to accurately quantify the influence of climate and human activities on the evolution of underlying surface characteristic parameters. However, due to the spatiotemporal heterogeneity of underlying surface parameters, it is often difficult to accurately quantify these relationships. In this study, using the Kuye River Basin (KRB) located in the northern Loess Plateau as the research object, we first used trend analysis and nonlinear regression methods to estimate the evolution characteristics of runoff and underlying surface parameter n. We then determined the contribution of runoff changes by using the elasticity coefficient method under the 9-year moving average window. The results showed that: (1) the KRB runoff underwent a sudden change in 1997, and the complex human activities are the main reasons for the sharp runoff decrease. (2) In addition to precipitation and potential evapotranspiration, temperature changes will alter the basin's underlying surface parameters, ultimately changing the runoff. Moreover, climate change first inhibited and then promoted the runoff reduction trend. (3) Human activities, represented by changes in vegetation coverage and coal mining, considerably influenced runoff evolution in KRB. More importantly, the change of runoff in the KRB caused by coal mining is approximately four times that of the normalized vegetation index. This study can improve the applicability of the Budyko framework in the Loess Plateau sub-basin and provide scientific guidance for water resource management.